2018
DOI: 10.1039/c8ta01818a
|View full text |Cite
|
Sign up to set email alerts
|

New anatase phase VTi2.6O7.2 ultrafine nanocrystals for high-performance rechargeable magnesium-based batteries

Abstract: A new kind of VTi2.6O7.2 ultrafine nanocrystals is designed via constructing substitutional solid solution, and it exhibits improved Mg2+ and Li+ storage performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…It is similar to LIBs and operates by shuttling the Li ions between the electrodes. [20][21] Currently, a plenty of literatures have been reported on hybrid MgÀ Li batteries with different cathodes, such as TiS 2 (1.4 V, vs. Mg/ Mg 2 + ), [22] Li 4 Ti 5 O 12 (0.5 V, vs. Mg/Mg 2 + ), [19] LiCrTiO 4 (0.62 V, vs. Mg/Mg 2 + ), [23] FeS 2 (0.7 V, vs. Mg/Mg 2 + ), [24] MLi 2 Ti 6 O 14 (0.62 V, vs. Mg/Mg 2 + ). [25] Nevertheless, the limited electrochemical performance of these hybrid MgÀ Li batteries is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is similar to LIBs and operates by shuttling the Li ions between the electrodes. [20][21] Currently, a plenty of literatures have been reported on hybrid MgÀ Li batteries with different cathodes, such as TiS 2 (1.4 V, vs. Mg/ Mg 2 + ), [22] Li 4 Ti 5 O 12 (0.5 V, vs. Mg/Mg 2 + ), [19] LiCrTiO 4 (0.62 V, vs. Mg/Mg 2 + ), [23] FeS 2 (0.7 V, vs. Mg/Mg 2 + ), [24] MLi 2 Ti 6 O 14 (0.62 V, vs. Mg/Mg 2 + ). [25] Nevertheless, the limited electrochemical performance of these hybrid MgÀ Li batteries is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The working principle of a hybrid Mg−Li batteries is shown in Figure a. It is similar to LIBs and operates by shuttling the Li ions between the electrodes . Currently, a plenty of literatures have been reported on hybrid Mg−Li batteries with different cathodes, such as TiS 2 (1.4 V, vs. Mg/Mg 2+ ), Li 4 Ti 5 O 12 (0.5 V, vs. Mg/Mg 2+ ), LiCrTiO 4 (0.62 V, vs. Mg/Mg 2+ ), FeS 2 (0.7 V, vs. Mg/Mg 2+ ), MLi 2 Ti 6 O 14 (0.62 V, vs. Mg/Mg 2+ ) .…”
Section: Introductionmentioning
confidence: 99%
“…24,64 The isovalent substitution of V 4+ (r ¼ 0.58Å) for Ti 4+ by Sheng et al was not found to improve intercalation capacity for Mg in anatase, but instead offered improved pseudocapacitive storage. 22 In light of the current discussion, we speculate that the smaller size of V 4+ compared to Ti 4+ does not cause lattice expansion, and is unlikely to inhibit the distortions discussed above.…”
Section: Discussion: the Role Of Frustrationmentioning
confidence: 60%
“…However the charge storage was predominantly of a faradaic pseudocapacitive type, rather than a diffusion-controlled intercalation mechanism. 22 The enhanced capacity reported by Koketsu et al suggests that there may be doping strategies that can make anatase a viable Mg battery cathode material. Conveniently, doped anatase has been studied as a Li-ion battery electrode material in previous experimental literature, and with improvements and changes in performance noted for a range of dopants including Ni, 23 Nb, 24,25 Sn, 26 Fe, 27 and Mo, 28 providing an indication of routes to explore.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27–31 ] However, the divalent Mg 2+ ions exhibit sluggish kinetics which originates from the strong polarizing nature and results in low or even no capacity in most cathode materials established for Li‐storage. [ 32–35 ] Choosing Mo 6 S 8 as the cathode material is a breakthrough on the way to RMBs and it still surpasses many of cathodes even today, especially in cycling stability. The Chevrel phase (CP) compound was first introduced in LIB in 1985, and also demonstrated high mobility of various ions (Ni 2+ , Zn 2+ , and Mg 2+ ).…”
Section: Introductionmentioning
confidence: 99%